브랜드명성수준에 따른 브랜드 스토리텔링의 효과 - 최수아; 정효선; 황윤용; Choi, Soow-A; Jung, Hyo-Sun; Hwang, Yoon-Yong (Journal of distribution science, 2014)
Purpose - Brands and products often play key roles in enabling consumers to experience a good attitude, resulting in mentally enacting a specific prototype and reliving the experience by retelling a specific story. Brand storytelling can function as an important tool for managing the brand. To successfully apply a firm's brand storytelling, it is important to prove the effectiveness of storytelling. Therefore, by utilizing the research of Escalas (1998) and Fog et al. (2005), a list of measurements for storytelling component quality (SCQ) was applied. In addition, customer attitudes toward brand storytelling were tested. In particular, if customers encounter a dynamic and interesting story, although the brand is not widely known, they can be in communion with the brand and establish an emotional connection (Hill, 2003). Thus, brand reputation was divided into two levels (high vs. low), and the difference in effectiveness between storytelling component quality and consumers' advertisement attitude, brand attitude, and purchasing intention was examined. Research design, data, and methodology - By using the measurement list used in Choi, Na, and Hwang (2013), 12 categories in the level of message quality, conflict quality, character quality, and plot quality were measured. In addition, categories of brand reputation, advertisement attitude, brand attitude, and purchasing intention were measured. The study was based on 181 final survey samples targeting undergraduate and graduate students in Gwangju Metropolitan City. Results - Consumer responses toward storytelling were researched in the context of brand characteristics or product attributes, such as brand reputation, differentiated from extant simple effects of storytelling. Some brands with high reputation enjoy a halo effect due to prior learning, while other brands with comparatively low reputation have trouble generating positive responses despite attempts to enhance the level of reputation or induce favorable attitudes. Although not all due to the component quality of storytelling, the case of brands with low reputation exerted more positive impact on consumer attitudes than did brands with high reputation. As mentioned earlier, consumer evaluation of the component quality of storytelling was categorized into advertising attitudes, brand attitudes, and purchase intention for this study; this provides managerial implications in other ways. The results imply that an effective application of storytelling could be an important emotional tool for the development of both brands with low brand awareness and of well-known brands. Finally, this study serves to increase consumers' understanding and ability in interpreting brand stories that marketers tell about themselves, as well as to highlight differential experiences with products by level of brand hierarchy. Conclusions - This research aimed to provide an objective guideline for storytelling component quality while considering brand awareness. Thus, brand reputation was considered for proving the baseline effectiveness of storytelling, and this study provided directions for strategic establishment of storytelling. Based on this, we conclude that in further studies, it will be necessary to systematically manage brand story by considering other situation variables and various story patterns, and studying their differences.